1996
DOI: 10.1016/s0006-3495(96)79865-x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion of water in biological tissues

Abstract: This article deals with the characterization of biological tissues and their pathological alterations. For this purpose, diffusion is measured by NMR in the fringe field of a large superconductor with a field gradient of 50 T/m, which is rather homogenous and stable. It is due to the unprecedented properties of the gradient that we are able not only to determine the usual diffusion coefficient, but also to observe the pronounced Non-Debye feature of the relaxation function due to cellular structure. The dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 22 publications
2
72
0
1
Order By: Relevance
“…The molecular motion is assumed independent of the preceding waiting time but dependent on the velocity at the starting point. Generally, as α decreases from the Galilei-invariant Gaussian at α = 1 to the Galilei-variant forms there is an increase in a long displacement tail which is in agreement with the effects on the propagators for the heterogeneous gels observed in this study and has been previously observed for heterogeneous porous media [54,55].…”
Section: Hydrodynamic Dispersion In Porous Mediasupporting
confidence: 92%
“…The molecular motion is assumed independent of the preceding waiting time but dependent on the velocity at the starting point. Generally, as α decreases from the Galilei-invariant Gaussian at α = 1 to the Galilei-variant forms there is an increase in a long displacement tail which is in agreement with the effects on the propagators for the heterogeneous gels observed in this study and has been previously observed for heterogeneous porous media [54,55].…”
Section: Hydrodynamic Dispersion In Porous Mediasupporting
confidence: 92%
“…It is a common practice to put a Wishart distribution (see definition below) prior, on the concentration matrix in multivariate analysis. Moreover, in the case of a Wishart distribution, a closed form expression for the Laplace transform exists and leads to a Rigaut-type asymptotic fractal law [16] which has been observed in many biological systems [8] (see explanation below).…”
Section: The Mixture Of Wisharts Model and Denoising Kernelmentioning
confidence: 96%
“…The Wishart distribution γ p, Σ is known to have the closed-form Laplace transform: (8) where (ϴ + Σ −1 ) ∈ n . Let f in Eq.…”
Section: Definition 1 [10] For σ ∈ N and For P Inmentioning
confidence: 99%
“…Indeed the time evolution of the concentration and velocity profile predicted by Fick or Darcy is described by exponential-type solution and, several deviations from experimental results have been found in scientific literature regarding fluid flows in biological tissues [4,5] usually referred to long-tails of the diffusion processes as well as through biological membranes [6,7]. The difference among Fick prediction and experimental results have been captured, recently, considering particle transport at nanometric scale by means of molecular dynamics simulations [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%